Sights and Sounds of Disgusting Abjections: The Monstrous Feminine in The Exorcist (1973) (Itinera, 2024)
The film The Exorcist contains many excessive and gross images, which made its repu- tation as a milestone in the history of horror. The representation of the possessed Regan as an abject creature entails the concept of monstrous feminine, revealing the terror that the patriarchy has towards the psychophysical development of women, who achieve emancipation through puberty. Regan becomes angry, opposes earthly authorities and God, and speaks of sex: in other words, she transforms from an “innocent” girl into an abject woman, which is sanctioned by the scene in which she masturbates with a crucifix and pushes her mother’s face onto her genitals. The Exorcist shows taboo behaviors be- fore re-establishing (male) order: the priests perform the exorcism by entering Regan’s body and the matriarchal home of the MacNeil family. Visual abjections are linked to Regan’s body vomiting green bile, urinating on the floor, initiating incest with her mother; her skin changes color, becomes covered with sores and pus, and her hair becomes greasy and disheveled. These disgusting alterations are related to the adolescent menarche, and they are instrumental in highlighting the battle between patriarchal structures and the dis- ruptive sexuality represented by the female body at the beginning of puberty. However, such representation not only is visual, but also aural: Regan’s voice is replete with exces- sive features, in terms of both form – the profanities she says – and substance – the acous- tic quality of the voice, which contains nonlinear analogues of animal sounds produced under duress. Regan is aurally “possessed”, since her demonic voice is not that of the teenager actress that visually plays the character (Linda Blair) but rather that of a mature woman (Mercedes McCambridge). The vocal sounds of the demon are in same cases di- alogue proper, but they are also used as non-verbal sound effects in order to denote Re- gan’s abnormality and elicit a disgusted reaction in the audience. The choice of McCam- bridge is interesting not only because of its raucous, wheezing sound, but also because of her connotation as queer. Regan’s vocal excess is queer itself, since Pazuzu is connoted as male while the possessed person is female and speaks with a female voice – although mannish. Such vocal excess reveals to Regan’s mother and to the rest of the characters the uncanny emergence of womanhood and sexual drive from the child’s psyche and body.
Keywords: Monstrous Feminine, Patriarchy, Psychology, Soundtrack